Effects of Instructional Materials (computer) in Promoting Secondary Schools Students’ Academic Performance in Computer Science in Kebbi State, Nigeria - Nura, Bawa (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2016)
The study examined the effects of instructional materials in promoting secondary schools students’ academic performance in computer science in Kebbi State, Nigeria. Quasi experimental with a pretest and post-test, non-equivalent comparison design was adopted. Purposive sampling was used to select two JSS3 intact classes of 31 and 34 students from Government Girls Secondary School Birnin Kebbi and Salamatu Hussaini Girls Secondary School Birnin Kebbi as experimental and control groups respectively to participate in the study. An instrument titled Computer Science Achievement Test (CSAT) was validated by experts and reliability co-efficient of 0.93 was obtained using Kuder Richardson 21 (KR-21). The instrument was used for the pretest and posttest. Two research questions were answered and the hypothesis formulated was tested at 0.05 level of significance. Data were analyzed using mean and z-test. Findings revealed that there was significant difference in the academic performance of the students taught using instructional material (computer) and those taught using conventional instruction. In favor of the experimental group (those taught using instructional material (computer)), thus instructional material was found effective. It was recommended among others that education board should commit itself to providing relevant and economically enhanced instructional materials to secondary schools and more computers should be provided to schools for effective delivery in the teaching of computer science in secondary schools.